Prevalence and Aetiology of Pathological Vaginal Discharge among Third- Trimester’ Women Attending Antenatal Care at Kampala International University Teaching Hospital - Bwaga, Ibrahim; Nzabandora, Emmanuel; Ubarnel, Almenares; Ivan Bonet, Fonseca; Echoru, Isaac; Atuhaire, Collins; Ssebuufu, Robinson (International Journal of Health Sciences and Research, 2017)
A vaginal discharge means any secretion originating from the vagina except blood. Pathological vaginal discharge predisposes to preterm labor and prematurity which is a leading cause of infant mortality in the world. Objectives: To determine prevalence and aetiology of pathological vaginal discharge among women in third trimester who attend Antenatal Care (ANC) at Kampala International University Teaching Hospital (KIUTH). Research methods: A cross-sectional study was carried out from February through April, 2017. 394 of the women in third trimester who attended ANC at KIUTH during the study period were recruited, and data was collected using structured interviewer-administered questionnaire and laboratory investigation on the vaginal discharge specimen. The data was analyzed with the use of SPSS software. Results: 45.2% of participants had pathological vaginal discharge. Vaginal Candidiasis largely contributed to pathological vaginal discharge (37.1%) while Trichomoniasis contributed the least (2.2%). Bacterial Vaginosis caused 10.1% of the pathological vaginal discharge while 50.6% was due to bacterial infections (of the total of 178 participants, 34.3% had Staphylococcus Species infection, Streptococcus infection at 1.7%, Klebsiella species at 3.4% and mixed infections at 1.1%). Conclusion: Some pregnant women in third trimester who attend ANC at KIUTH actually harbor pathogenic organisms (Trichomonas spp, Candida spp, Staphylococcus spp, Streptococcus spp, E. coli and Bacterial vaginosis) and these organisms put them at risk of poor perinatal outcomes like premature rupture of membranes, chorioamnionitis, etc. Some pregnant women in third trimester have pathogenic bacterial colonization that requires detection and necessary care given.
Keywords: Pathological Vaginal Discharge; Antenatal Care